2005
DOI: 10.1111/j.1551-2916.2005.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Toughness Silicon Carbide as Armor

Abstract: Silicon carbide, with single‐edge precracked beam (SEPB) toughness greater than 7 MPa·m1/2, was made by hot‐pressing using Al–B–C (ABC) or Al–Y2O3 (YAG) as additives. The hardness of SiC processed with a liquid phase was always less than SiC densified without a liquid phase despite having a similar or finer grain size. With increasing Al content, the ABC system changed from trans‐ to intergranular fracture with a drop in hardness and a two‐ to threefold increase in SEPB toughness. Strength and Weibull modulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 31 publications
(55 reference statements)
3
55
0
Order By: Relevance
“…Due to their extremely brittle nature, most ceramics possess an inverse relationship between hardness and toughness [19,54,55]. To examine this behavior for the ceramics investigated in this study, a plot of Vickers hardness versus fracture toughness is generated in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their extremely brittle nature, most ceramics possess an inverse relationship between hardness and toughness [19,54,55]. To examine this behavior for the ceramics investigated in this study, a plot of Vickers hardness versus fracture toughness is generated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic microstructural toughening mechanisms can activate various fracture processes. The inclusion of glassy [1] or metallic [19] secondary phases has been shown to decrease the brittleness and increase the fracture toughness value of ceramics. Newer processing techniques, such as reaction bonding, have been used to manufacture ceramics with increased fracture toughness while minimally compromising other material properties, such as density and hardness, compared to similar sintered ceramics [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…6 Since then, several tens of publications reported the phase until recently. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, Hillebrecht and Meyer analyzed the structure of "Al 8 B 4 C 7 " and reported that the correct molecular formula of the compound is Al 3 BC 3 . 26 Several papers have described the properties and structure of Al 3 BC 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Because of their brittle nature, ceramics and glasses are susceptible to localized surface damage in the form of cracking when subjected to impact by foreign objects. [6,7] Much work has been carried out on the dynamic impact behaviour of ceramics and glasses. [1][2][3][4][5] Tests have been carried out using small ceramic or metallic spheres, impacting at high speed in so-called ballistic tests.…”
mentioning
confidence: 99%